Assessment of circular and elliptical absorber tube in solar parabolic trough collector. Issue 1 (31st December 2022) - Jebasingh, V. K.; Divya Johns, J.; Arunkumar, T.
Abstract : Solar parabolic trough collector, the best concentrated solar collector technique for electricity generation and for heat application industries, has been studied by many researchers. In this paper, the ordinary circular absorber is replaced with an elliptical absorber and its performances have been studied. The function of the absorber tube in parabolic trough collector is to absorb and transfer the heat to the working substances or the fluid used in the absorber. The working fluid considered over here is water which is the best operating medium in direct steam generation. The transmission of water in the absorber tube is analysed with three flow rates (0.014, 0.021 and 0.028 kg/s). An experimental test was done in Tamil Nadu, Southern part of India, which experiences a better temperature throughout the year. The experiment was conducted from June 2017 to July 2018. The performance improvement focused on the useful heat transfer rate, outlet temperature of the working fluid, temperature gradient, overall heat transfer rate, the thermal losses and the collector efficiency.